Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 8985 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Didelphis virginiana Kerr, 1792" ] } The dataset includes 8985 records from 117 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0016702-151016162008034/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences